Demand forecasting of postal services of Česká pošta, s.p. - Motyková, Jana; Švadlenka, Libor; Zákorová, Eva (Žilinská univerzita, 2016)
The aim of this paper is to analyse statistical data regarding of provided services of Česká pošta, s.p. in the period 2002 – 2015. The information obtained from the analysis of the realized traffic volume will be the base for the forecasting of postal services for the year 2016 that will be performed by the methods of mathematical statistics. In first step of the statistical analysis it will be recognized the trend components of the time series by the growth characteristics. If the existence of the trend component is confirmed, estimation of trend parameters will be performed. Then will be performed the chart analysis. The results from the analysis will be confirmed or disproved by the theil’s coefficient.
Předpověď poptávky po poštovních službách České pošty, s.p.
Keywords: postal services; demand of postal services; time series; statistical analysis; časové řady; poptávka po poštovních službách; poštovní služby; statistická analýza